Letter (copy) : Food for Spain - Citrine, Walter, 1887-1983
030-0066-002 International. WMC/EAB. 14th September 1938. Mr. W. Elger, J.P., Scottish Trades Union Congress, 33 Elmbank Crescent, Glasgow. Dear Mr. Elger, FOOD FOR SPAIN. Further to our conversation on the telephone with your secretary yesterday afternoon, regarding the despatch of a consignment of food to Spain, we have now received a communication from Comrade Schevenels, wherein he suggests that the consignment should be sent to Barcelona. He also suggests that the long sea route should be avoided, and that the goods should be sent via Bordeaux across France to Cervere, where they can be loaded on to lorries for Barcelona. With regard to the despatch of the goods, they should be addressed for delivery to: Senor Calvet, Agente de Aduanas, Cervere, and consigned to: Fondo de Solidaridad Internacional, Enrique Santiago, Aragon 300, Barcelona. We shall be glad if you will be good enough to ask Mr. Tewson to telephone our International Department when next he is in your office. Yours sincerely, General Secretary. 292/946/30/66